Examining Effectiveness of Group Cognitive-Behavioral Therapy for Externalizing and Internalizing Disorders in Urban Schools. (July 2016) - Eiraldi, Ricardo; Power, Thomas J.; Schwartz, Billie S.; Keiffer, Jackie N.; McCurdy, Barry L.; Mathen, Manju; Jawad, Abbas F.
This article presents outcome data of the implementation of three group cognitive-behavioral therapy (GCBT) interventions for children with externalizing behavior problems, anxiety, and depression. School counselors and graduate students co-led the groups in two low-income urban schools. Data were analyzed to assess pre-treatment to post-treatment changes in diagnostic severity level. Results of the exploratory study indicated that all three GCBT protocols were effective at reducing diagnostic severity level for children who had a primary diagnosis of an externalizing disorder, anxiety disorder, or depressive disorder at the clinical or intermediate (at-risk) level. All three GCBT protocols were implemented with relatively high levels of fidelity. Data on the effectiveness of the interventions for reducing diagnostic severity level for externalizing and internalizing spectrum disorders and for specific disorders are presented. A discussion of implementation of mental health evidence-based interventions in urban schools is provided.